2018
DOI: 10.3847/1538-3881/aad599
|View full text |Cite
|
Sign up to set email alerts
|

WEIRD: Wide-orbit Exoplanet Search with InfraRed Direct Imaging

Abstract: We report results from the Wide-orbit Exoplanet search with InfraRed Direct imaging, or WEIRD, a survey designed to search for Jupiter-like companions on very wide orbits (1000-5000 au) around young stars (<120 Myr) that are known members of moving groups in the solar neighborhood (<70 pc). Companions that share the same age, distance, and metallicity as their host while being on large enough orbits to be studied as "isolated" objects make prime targets for spectroscopic observations, and they are valuable ben… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 124 publications
(195 reference statements)
6
20
0
Order By: Relevance
“…HD 25284B was flagged as 0.5" binary in WDS from Tycho, but this companion was not retrieved in our SPHERE observations (Langlois et al 2021) and then the target was kept in the SHINE statistical analysis as an isolated object. Nothing found at large separation by WEIRD (Baron et al 2018). The companion we found around the primary of this system is a new discovery.…”
Section: Idmentioning
confidence: 51%
“…HD 25284B was flagged as 0.5" binary in WDS from Tycho, but this companion was not retrieved in our SPHERE observations (Langlois et al 2021) and then the target was kept in the SHINE statistical analysis as an isolated object. Nothing found at large separation by WEIRD (Baron et al 2018). The companion we found around the primary of this system is a new discovery.…”
Section: Idmentioning
confidence: 51%
“…Stamatellos et al 2007aStamatellos et al , 2011Stamatellos & Whitworth 2009b). Observational surveys indicate that only a small fraction of M dwarfs (less than ∼10%) host wide orbit planets and this also holds for higher-mass stars (Brandt et al 2014;Bowler et al 2015;Lannier et al 2016;Reggiani et al 2016;Galicher et al 2016;Bowler 2016;Vigan et al 2017;Baron et al 2018;Stone et al 2018;Wagner et al 2019;Nielsen et al 2019) (see review by Bowler & Nielsen 2018). These surveys typically explore a region out to a few hundred AU from the central star (or even a few thousand AU, Durkan et al 2016;Naud et al 2017) and they are sensitive down to Jupiter-mass planets.…”
Section: Introductionmentioning
confidence: 99%
“…Durkan et al (2016) find companions with 0.5-13 M Jup at separations of 100-1000 au occur with an upper frequency limit of 9% based on a sample of 121 stars. Baron et al (2018) probe further separations of 1000-5000 au in their 177 star sample, finding an occurrence rate of < 3% for 1-13 M Jup companions. As mentioned previously, both surveys searched for wide companion systems in young moving groups that are closer (< 100 pc) and older (> 10 Myr) than the regions from which our target sample was created.…”
Section: Optimizing the Search For Wide Pmcs With Spitzermentioning
confidence: 87%
“…Note that the remaining residuals appear similar to the noise near the primary star, indicating a good fit. recently, Baron et al (2018) reported first results from the Wide-orbit Exoplanet search with InfraRed Direct Imaging (WEIRD) survey constraining the occurrence of Jupiter-like companions on orbits between 1000 and 5000 au. These studies focused their investigations on regions closer (d < 100 pc) and older (τ > 10 Myr) than the regions we analyze in this work (d > 100 pc; τ < 10 Myr).…”
Section: Discussionmentioning
confidence: 99%